Technology commercialization strategy in a dynamic context: Developing specialized complementary assets in entrepreneurial firms - David H. Hsu; Simon Wakeman (European School of Management and Technology (ESMT), 2013)
A firm that lacks the specialized complementary assets necessary to commercialize an innovation faces a trade-off between contracting with an incumbent to access those assets and integrating downstream into commercialization. According to the framework developed in the prior literature, under a strong appropriability regime the innovator is likely to be better off contracting with an incumbent (as long as it can negotiate reasonable terms). However, we argue that if the innovator can learn from its experience in product commercialization, and thereby build its own commercialization capabilities, then the benefits of integrating downstream may outweigh the opportunity costs of learning and foregone profits. Alternatively, by engaging in joint commercialization, the innovator may be able to avoid these opportunity costs, albeit at the expense of higher inter-organizational governance costs. We illustrate the relationship between the choice of commercialization mode, commercialization experience, and performance in the context of the pharmaceutical industry. Specifically, we study how commercialization mode and experience affects the likelihood of drug approval. We find that when innovators lacking commercialization experience participate in the commercialization process though either joint commercialization or by commercializing alone, the product is less likely to be approved. However, innovators that have participated in the commercialization process in the past are more likely to successfully commercialize subsequent innovations under joint commercialization than those which have only contracted the commercialization to an incumbent. The results suggest that in some circumstances participating in the commercialization process, either through self-commercialization or by engaging in joint commercialization, may be the optimal strategy even for firms without the requisite complementary assets.
urn:nbn:de:101:1-2013120627863
Keywords: 650; Complementary assets; technology commercialization strategy; entrepreneurial firms; strategic alliances; alliance structure; Unternehmensgründung; Strategische Allianz; Lernende Organisation; Produktentwicklung; Biotechnische Industrie; USA